1991
DOI: 10.1093/nar/19.20.5653
|View full text |Cite
|
Sign up to set email alerts
|

Different complexes are formed on the 3′ end of histone mRNA with Nuclear and polyribosomal proteins

Abstract: Specific protein-RNA complexes are formed by incubating a synthetic histone mRNA 3' end (a 30 nucleotide stem-loop structure) RNA with extracts of either nuclei or polyribosomes. The complex formed between the stem-loop and nuclear proteins has a lower electrophoretic mobility than the complex formed between the stem-loop and polyribosomal proteins. Binding of the synthetic 3' end by both polyribosomal and nuclear proteins is abolished when two of the conserved uridine residues in the loop are replaced with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 40 publications
4
64
1
Order By: Relevance
“…We have shown here specifically that the SLBP we cloned is the major protein that binds to the 3' end of histone mRNA as detected by the RNA-binding assay. Using antibodies specific for the carboxyl terminus of the SLBP, we have demonstrated that the SLBP is the major binding activity present in both the nucleus and the polyribosomes, in agreement with our previous conclusion that the same polypeptide functions in both compartments (Pandey et al 1991;Dominski et al 1995;Hanson et al 1996). There are two forms of SLBP detected by Western blotting (Figs.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We have shown here specifically that the SLBP we cloned is the major protein that binds to the 3' end of histone mRNA as detected by the RNA-binding assay. Using antibodies specific for the carboxyl terminus of the SLBP, we have demonstrated that the SLBP is the major binding activity present in both the nucleus and the polyribosomes, in agreement with our previous conclusion that the same polypeptide functions in both compartments (Pandey et al 1991;Dominski et al 1995;Hanson et al 1996). There are two forms of SLBP detected by Western blotting (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…A similar size was obtained when the human SLBP was synthesized in frog oocytes after injection of the mRNA or in a wheat germ translation system (not shown). This mobility is consistent with the cloned cDNA representing the previously characterized SLBP (Pandey et al 1991;Hanson et al 1996), and suggests that the discrepancy in molecular mass is attributable to an anomalous mobility of the SLBP on SDS--polyacrylamide gels (Fig. 4B, lane 1).…”
Section: Diaryrrkllinefgrrerrsssgssdskds Sthgemetdpavitr 134supporting
confidence: 85%
See 3 more Smart Citations